Elaboración de bioempaques a partir de almidones nativos y aceites esenciales prolongando vida útil en fresas - Beltran, Camila Andrea Ubaque; Florez, Ivan Fernando (Revista Colombiana de Investigaciones Agroindustriales, 2018)
The packaging protects and preserves the products of contaminants, especially of biological type. Bio-active packaging, made up of native starch, essential oils and natural extracts, was elaborated for this research, prolonging the useful life of Strawberries. Bio-packaging emerges as an alternative to reduce environmental pollution generated by the indiscriminate use of plastic of synthetic origin. We worked with raw materials such as: Malanga, Achira, Flor de un día, Paturro blanco, Coyo and Bore) with characteristics of plastic films of natural origin from Cundinamarca, each raw material presented usable percentage of starch; Malanga had the highest percentage of 38% starch. Natural essential oils were used: Cinnamon, Toronjil, Rosemary, Laurel, Albaca, Thyme and Propolis ethanol extract, obtained by solvent extraction, which present active principles recognized for their antimicrobial activity, essential oils of Rosemary, Cinnamon and extract ethanol from Propolis, showed greater inhibitory capacity against (Botritys cinerea, E. coli and S. aureus), strains analyzed due to their incidence in the useful life of the strawberries. The measurement of the useful life was obtained by means of plate count results, analyzing strawberries evaluated at 4 ° C, 18 ° C, 22 ° C and 16 ° C. Samples were analyzed with and without the Bio-packing, modeled with the Arrhenius equation, the result showed that the use of native starch with the presence of essential oils inhibits microbial growth, increasing the useful life of strawberries by 46% the decrease in the speed of microbial growth